BITMOJI 3-DIMENSIONAL AVATARS AS A VISUAL TOOL TO IMPROVE THE ABILITY OF GRADE 7 STUDENTS IN USING PREPOSITIONS OF PLACE - Agustin, Michael Christophe; Villanueva, Louie; Irish R. Arucan, Frances; Jan L. Galeon, Roselle; F. Jose, Tristan (English Study Program University of Pasir Pengaraian, 2024)
This study aimed to improve the ability of the Grade 7 students in using prepositions of place by integrating Bitmoji 3-Dimentional Avatars. The participants were 64 Grade 7 students who were officially enrolled at Ilocos Norte College of Arts and Trades during the second semester of the Academic Year 2022-2023. Bitmoji is a free application and a website where users can design their 3-dimensional avatars. With its features, the avatars of the students were created and incorporated into the MS PowerPoint presentation slides about prepositions of place. The data on the students’ ability in using prepositions of place were gathered using a 30-item test based on the intended competencies of English 7. To support the findings, the student’s perceptions on the avatars were also gathered through unstructured interviews and pre- and post-questionnaire. Frequency, percentage, and mean, were used to treat the data gathered. Results reveal that the students’ mean score on their pre-test is 8.5 or Below Average, while 19.50 on the post-test or Above Average. Likewise, in the test of difference, the t-value of 13.80 with a probability of .001, which is lower than the .05 level of significance, implies that there is an evident improvement in the student’s’ ability in using prepositions of place with the integrated pedagogical features of Bitmoji Avatars. Thus, the study recommends that teachers should maximize applications, such as Bitmoji, for their engaging features, which assist the students as visual learners, and foster teaching grammatical points, such as prepositions.